Formaldehyde induces hyperphosphorylation and polymerization of Tau protein both in vitro and in vivo - Lu, Jing; Miao, Junye; Su, Tao; Liu, Ying; He, Rongqiao (Biochimica et biophysica acta, 2013)
Chronic formaldehyde exposure leads to memory impairment and abnormal elevation of endogenous formaldehyde has been found in the brains of Alzheimer's disease (AD) patients. Hyperphosphorylated Tau protein with subsequent aggregates as neurofibrillary tangles (NFTs) is one of the typical pathological characteristics in AD brains. The mechanism underlying abnormally elevated concentrations of endogenous formaldehyde that induce Tau hyperphosphorylation is unknown. N2a cells and mice were treated with formaldehyde for different time points, then Western blotting and immunocytochemistry were utilized to determine the phosphorylation and polymerization of Tau protein. HPLC was used to detect the concentration of formaldehyde in cell media. Under formaldehyde stress, Tau became hyperphosphorylated, not only in the cytoplasm, but also in the nucleus of neuroblastoma (N2a) cells, and mouse brains. Polymers of cellular phospho-Tau were also detected. Significant accumulation of glycogen synthase kinase-3β (GSK-3β) in the nucleus of N2a and mouse brain cells, and elevation of its phosphorylation at Y216, was observed under formaldehyde stress. Formaldehyde-induced Tau hyperphosphorylation was blocked in the presence of LiCl and CT99021, inhibitors of GSK-3β, and by RNAi interference. Formaldehyde, which may cause age-related memory loss, can act as a factor triggering Tau hyperphosphorylation via GSK-3β catalysis and induces polymerization of Tau. Investigation of formaldehyde-induced Tau hyperphosphorylation may provide novel insights into mechanisms underlying tauopathies. •Formaldehyde can induce hyperphosphorylation of Tau protein in both N2a cells and mouse brain.•Hyperphosphorylated Tau induced by formaldehyde occurs not only in cytoplasm but also in nucleus of cell.•GSK-3β is involved in the formaldehyde-induced hyperphosphorylation of Tau.•Hyperphosphorylated Tau induced by formaldehyde forms ThS-positive polymers in cells.